Disruption of the dopamine D3 receptor gene produces renin-dependent hypertension. - L D Asico; C Ladines; S Fuchs; D Accili; R M Carey; C Semeraro; F Pocchiari; R A Felder; G M Eisner; P A Jose (The Journal of Clinical Investigation, 1998)
Since dopamine receptors are important in the regulation of renal and cardiovascular function, we studied the cardiovascular consequences of the disruption of the D3 receptor, a member of the family of D2-like receptors, expressed in renal proximal tubules and juxtaglomerular cells. Systolic and diastolic blood pressures were higher (approximately 20 mmHg) in heterozygous and homozygous than in wild-type mice. An acute saline load increased urine flow rate and sodium excretion to a similar extent in wild-type and heterozygous mice but the increase was attenuated in homozygous mice. Renal renin activity was much greater in homozygous than in wild-type mice; values for heterozygous mice were intermediate. Blockade of angiotensin II subtype-1 receptors decreased systolic blood pressure for a longer duration in mutant than in wild-type mice. Thus, disruption of the D3 receptor increases renal renin production and produces renal sodium retention and renin-dependent hypertension.